PREVALENCE OF OVERWEIGHT AND OBESITY ON PREGNANCY (Fiep Bulletin - online, 2015)
Introduction: Obesity has been considered a public health matter, since its significant increase in developed and sub developed countries. It occurs within various segments of the population and it has been noticed an increase on the prevalence of pregnant woman, attached to a chain of pregnancy, maternal and neonatal complications. Methodology: Documental, descriptive study, by a quantitative approach, performed in a Family Health Unit in Cajazeiras city with a sample of 156 pregnant women, from anthropometric data collected in the perinatal form of primary care. Goal: To know the prevalence of overweight and obesity in pregnant woman. Results showed that most of the pregnant women were married, aged from 20 to 35 years old, with 9+ years of study and that, according to the anthropometric evaluation, most of them presented overweight/obesity. By this research it is possible to conclude that overweight and obesity need a wider highlight and attention ahead national women's health support politics by the repercussion on maternal health and fetal/perinatal complications, turning the introduction of the promotional and preventive actions that incorporate women as an active subject in regards to caring for their health a needing.
Keywords: Pregnancy; Obesity; Overweight.